(untitled) (The Research of Medical Science Review, 2025)
Objectives: This study aimed to (1) examine the relationship of growth mindset and stress with psychological wellbeing among medical students, (2) assess the mediating role of self-regulation skills in this relationship, and (3) evaluate the combined influence of growth mindset and stress on psychological wellbeing through self-regulation skills. Methods: A quantitative, correlational research design was employed. Data were collected from 374 medical students through a self-administered online questionnaire. The study utilized standardized instruments: Growth Mindset Scale, Perceived Stress Scale, Self-Regulation Questionnaire–Short Version, and the Ryff Psychological Wellbeing Scale. SPSS version 25 was used to perform descriptive statistics, Pearson correlations, mediation analysis (using Hayes' PROCESS macro), and multiple regression analysis. Results: Growth mindset was positively correlated with psychological wellbeing (r = .47, p < .01) and negatively correlated with stress (r = –.38, p < .01). Stress was inversely related to wellbeing (r = –.43, p < .01). Mediation analysis confirmed that self-regulation partially mediated the relationships between both growth mindset and stress with psychological wellbeing. Multiple regression analysis revealed that growth mindset (β = .30), stress (β = –.31), and self-regulation (β = .34) significantly predicted psychological wellbeing (R² = .54, p < .001). Conclusion: The findings highlight self-regulation skills as a critical psychological mechanism that buffers the negative effects of stress and enhances the positive influence of growth mindset on mental wellbeing. Targeted interventions focusing on mindset and behavioral self-regulation may support emotional resilience and promote mental health in medical education.